Solvent-mediated conductance increase of dodecanethiol-stabilized gold nanoparticle monolayers - Reissner, Patrick A.; Tisserant, Jean-Nicolas; Sánchez-Ferrer, Antoni; Mezzenga, Raffaele; Stemmer, Andreas (Beilstein Journal of Nanotechnology, 2016)
Gold nanoparticle monolayers provide convenient templates to study charge transport in organic molecules beyond single junction techniques. Conductance is reported to increase by several orders of magnitude following immersion of alkanethiol-stabilized gold nanoparticle monolayers in a solution containing conjugated thiol-functionalized molecules. Typically, this observation is attributed to molecular exchange. Less attention has been paid to the role of the solvent alone. Here, we report on an increase in conductance of dodecanethiol-stabilized gold nanoparticle monolayers on Si/SiO2 by an average factor of 36 and 22 after immersion in pure ethanol (EtOH) and tetrahydrofuran (THF), respectively. Analysis by scanning electron microscopy (SEM) and small-angle X-ray scattering (SAXS) reveals a solvent-induced decrease in lattice constant of close-packed monolayers. We compare the conductance of the monolayer after molecular exchange with two different oligophenylenes to shed light on the respective contribution of the solvent-induced structural change and the molecular exchange itself on the conductance increase.
Keywords: molecular electronics; molecular exchange; percolation networks; Self-assembly